ANALISIS SANITASI DAN CEMARAN MIKROORGANISME IKAN ASAP LELE DI BENGKULU - Julman hadi; Lina widawati (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2015)
Smoked catfish is one way to preserve fish processing and at the same time using a combination of heating and the addition of a natural chemical compound derived from wood smoke . In smoked fish processing industry Kolman father is a business that still has not been simple or traditional improve the quality of production . Therefore there should be a study to improve the quality of processed fish products asap so consumers can be assured of the security for , but it also can provide benefits for processing. This study aims to determine the quality of smoked fish processed products based on parameters determine the number of microorganisms and sanitary conditions of smoked fish processing business in the District Muaro Bangkahulu catfish . The research was conducted in the smoked fish industry Mr. Kolman . Laboratory test was conducted on the TPC tests on samples of smoked fish. Method in this study include sampling father smoked fish industry Kolman located in the dike district governor Muaro bagkahulu . With smoked fish storage treatment for 0 , 6, and 7 days later TPC test sample . The results showed that the testing laboratory to TPC in smoked fish samples from day 0 as 10.0000 , on the 6th and 7th is 400,000 to 670,000 . Where up to the 7th day of storage of smoked fish samples had crossed the threshold SNI smoked fish that is 5 X 105 so it is not suitable for consumption .Keywords : Analysis, of sanitation, microorganism contamination, smoked catfish